The Incidence of Intraoperative Hypertension and Risk Factors for its Development during Thyroid Surgery. (November 2013) - Kalezic, Nevena; Stojanovic, Marina; Milicic, Biljana; Antonijevic, Vesna; Sabljak, Vera; Markovic, Dejan; Zivaljevic, Vladan
<x xml:space="preserve">Abstract</x> We studied the influence of demographic characteristics, comorbidity, and type and duration of surgery and anesthesia on the occurrence of intraoperative hypertension (IOHTA). Logistic regression analyses were used in order to determine the predictors of occurrence of IOHTA. More than 60% of our patients had IOHTA. Multivariate analysis showed that independent predictors for IOHTA were older age, BMI 25 kg/m2, and hypertension as a coexisting disease. Hypertension is common during thyroid surgery, and a significant number of patients remained hypertensive during the postoperative period.